Bitter root. Volume four, The next movement - Walker, David, 1968-; Brown, Chuck (Comic book author) (The Bitter Root, 2025)
"It is 1964, the height of the Civil Rights Movement. A group of activists have gone missing, and a new generation of the Sangerye family must face a menace far worse than anything their ancestors have ever encountered. The monstrous jinoo--creatures born out of hate and racism--have evolved into a threat that few people are willing to acknowledge, and even fewer know how to fight." -- back cover.